Oracle database 11g PL/SQL programming workbook [ - McLaughlin, Michael [ (Michael J.)]; Harper, John M. (McGraw-Hill, 2010)
"Master PL/SQL through the hands-on exercises, extensive examples, and real-world projects inside this Oracle Pressguide. Filled with best practices, Oracle Database 11g PL/SQL Programming Workbook covers all the latest features and enhancements of the language. Mastery checks at the end of each chapter reinforce the material covered, and sample code from the book is available for download. Even experienced Oracle professionals will benefit from this practical resource"--Resource description p